Pengaruh Institutional Ownership, Sales Growth, Dan Faktor Lainnya terhadap Financial Distress - Laurensari Devi; Julisar Surjadi (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
The purpose of this study is to obtain empirical evidence the influence of institutional ownership, independent commissioner, managerial ownership, audit committee, sales growth, operating capacity, liquidity and firm size on financial distress. The population in this research is manufacturing companies listed on Indonesia Stock Exchange (IDX) during the period 2020-2023 with a research period of 2021- 2023.The sample was determined using the purposive sampling method, resulting in 74 manufacturing companies and 222 data. The analysis data used multiple linear regression and was processed using the Statistical Package for the Social Sciences (SPSS). The results of this study indicate that independent commissioner, operating capacity, liquidity and firm size have an effect on financial distress. While institutional ownership, managerial ownership, audit committee and sales growth no significant effect on financial distress. These findings provide both theoretical and practical implications. Theoretically, this study enriches the financial distress and corporate governance literature by demonstrating that governance mechanisms and financial performance indicators do not equally influence the likelihood of financial distress. Practically, company management should strengthen the role of independent commissioners, improve asset utilization efficiency, maintain adequate liquidity, and optimize firm growth to minimize financial distress risk. Investors are also encouraged to consider governance quality and financial indicators when evaluating investment decisions, while regulators may use these findings to strengthen governance policies aimed at improving corporate financial sustainability.